Forging partnerships for health equity research: transformative capacity-building for community-academic teams - Valdez, Carmen R.; Petruzzi, Liana; Schnarrs, Phillip W.; Banks, Tasha; Coombe, Chris M.; Israel, Barbara A. (Frontiers in Public Health, 2025)
BackgroundCommunity-based participatory research (CBPR) is essential for translating and increasing the overall uptake of evidence-based interventions in community settings. Yet a limited number of academic and medical institutions provide structured and formal training on how to conduct high-quality CBPR or develop academic-community partnerships.MethodsBuilding upon a capacity-building program, we developed and implemented a year-long academic partnership training program. It consisted of a 2.5-day intensive short course, bimonthly didactic webinars, and year-long mentoring, as well as seed funding. Five dyads of academic researchers from universities in Texas and their community partners completed the program (n = 10) between May 2023 and May 2024. A mixed methods evaluation via a survey with closed- and open-ended questions was conducted at the end of the 12 months to evaluate satisfaction with the program and impact.ResultsNine out of the ten participants reported the program was excellent or very good, and all participants found the mentoring component and didactic sessions to be “transformative.” Participants highlighted the importance of forming close relationships with their partners and other teams, peer mentorship, and having a space to discuss challenges associated with CBPR. Both academic and community participants reported making significant progress on their research projects including local, state and federal conference presentations, applying for and securing grant funding, and submitting peer-reviewed manuscripts. They created tools that were helpful for their community.DiscussionDedicated training in CBPR practices for community practitioners and academics in the same space can build capacity for health equity research and initiatives. Using a combination of didactic and experiential learning opportunities, in addition to peer and formal mentorship, allowed for considerable growth among participants. Importantly, academics developed understanding and interest in community projects, and community members developed interest in research and appreciation for academic institutions. Suggestions for improving the program are also discussed.